The Effect of Chronic Intermittent Hypobaric Hypoxia on Sleep Quality and Melatonin Serum Levels in Chilean Miners - Calderon-Jofre, Rodrigo; Moraga, Daniel; Moraga, Fernando A. (Frontiers in Physiology, 2022)
High-altitude mining is an important economic resource for Chile. These workers are exposed to chronic intermittent hypobaric hypoxia (CIHH), which reduces their sleep quality and increases the risk of accidents and long-term illnesses. Melatonin, a hormone produced by the pineal gland, is a sleep inducer that regulates the circadian cycle and may be altered in populations subjected to CIHH. This work aimed to assess the relationship between altitude, sleep quality, and plasma melatonin concentrations in miners with CIHH exposure. 288 volunteers were recruited from 5 altitudes (0, 1,600, 2,500, 3,500 and 4,500 m). All volunteers worked for 7 days at altitude, followed by 7 days of rest at sea level. We performed anthropometric assessments, nocturnal oximetry, sleep quality and sleepiness surveys, and serum melatonin levels upon awakening. Although oxygen saturation progressively decreased and heart rate increased at higher altitudes, subjective perception of sleep quality was not significantly different, and sleepiness increased in all groups compared to population at sea level. Similarly, melatonin levels increased at all assessed altitudes compared to the population at sea level. These data confirm that sleep disturbances associated with CIHH increase morning melatonin levels. Therefore, this hormone and could potentially serve as a biomarker of sleep quality.